2011
DOI: 10.1007/s11010-011-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin promotes cholesterol efflux from adipocytes related to PPARgamma–LXRalpha–ABCA1 passway

Abstract: Curcumin affects the functions of adipocytes. But it is not known whether curcumin has some effect on the cholesterol efflux process of adipocytes. Rabbit subcutaneous adipocytes were incubated with 5, 10 and 20 μg/ml curcumin for 24 h. The cholesterol efflux onto apoAI was assessed, and the peroxisome proliferators-activated receptor (PPAR) γ, liver X receptor (LXR) α and ATP-binding cassette transporter A1 (ABCA1) mRNA expression in adipocytes were quantified by reverse-transcription polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Increased PPARγ expression has been shown to promote cholesterol efflux through LXRα in macrophages [54] and adipocytes [55]. LXRs act as cholesterol sensors, inducing the transcription of genes that protect cells from cholesterol overload, regulating reverse cholesterol transport (RCT), cholesterol biosynthesis and cholesterol absorption/excretion [56].…”
Section: Discussionmentioning
confidence: 99%
“…Increased PPARγ expression has been shown to promote cholesterol efflux through LXRα in macrophages [54] and adipocytes [55]. LXRs act as cholesterol sensors, inducing the transcription of genes that protect cells from cholesterol overload, regulating reverse cholesterol transport (RCT), cholesterol biosynthesis and cholesterol absorption/excretion [56].…”
Section: Discussionmentioning
confidence: 99%
“…When 3T3-L1 adipocytes were treated with 5, 10 and 20 µM of curcumin, the palmitic acid oxidation was 1.1-, 1.3-, and 2.0-fold higher than it in control 3T3-L1 cells, respectively; and mRNA expression levels of CPT-1 were 1.8-, 3.4-, and 3.8-fold higher than them in control 3T3-L1 cells, respectively [136]. In addition, Dong et al demonstrated that curcumin increases cholesterol efflux by activating and up-regulating the expression of liver X receptor (LXR) and ATP-binding cassette A1 (ABCA1) in subcutaneous adipocytes isolated from rabbits [135]. …”
Section: Curcuminmentioning
confidence: 99%
“…Recruitment and infiltration of macrophages into expanded adipose tissue can increased its local inflammatory response. Inhibitory effect of curcumin on chemotaxis and release of MCP-1 from adipocytes [130, 135] may partially contribute to its anti-inflammatory activity. When RAW 264.7 macrophages were treated with adipose tissue-conditioned medium containing 0.1 to 10 µM curcumin, the migration of macrophages was inhibited in a dose-dependent manner [142].…”
Section: Curcuminmentioning
confidence: 99%
“…In a mouse macrophage study, Zhou et al (2014) found that curcumin prevents a decrease in thrombospondin-4 induced by oxidized low-density lipoprotein (ox-LDL) to inhibit cell interaction. Furthermore, Dong et al (2011) found that curcumin can affect the cholesterol efflux from adipocytes by regulating the PPAR-LXR-ABCA1 pathway. On the basis of this study, Zhao et al (2012) demonstrated that curcumin reduces cholesterol accumulation in foam cell development by downregulating SR-A and upregulating ATP-binding cassette transporter 1 (ABCA1) using proteasome-and liver X receptor alpha (LXRa)-dependent pathways, respectively.…”
Section: Introductionmentioning
confidence: 99%